REVIEW OF ONLINE LOAN PROBLEMS IN INDONESIA: Perspective of Fiqh Muamalah and DSN-MUI Fatwa - Anggraini, Misi; Hulwati, Hulwati; Duhriah, Duhriah (Jurnal Studi Islam dan Sosial, 2025)
The rapid development of online loans has led to various social and economic issues, highlighting the need for studies from the perspective of fiqh muamalah and the fatwa of the National Sharia Council of the Indonesian Ulama Council (DSN-MUI) as references for Islamic law in financial transactions. This goal clearly emphasizes the specific aspects of the study to be achieved. The research will involve a literature review and qualitative analysis of regulations, DSN-MUI fatwas, and literature on fiqh muamalah. Data collection methods may include documentation of fatwas and regulations relevant to online loans and a comparative analysis of existing practices. This approach aims to provide a comprehensive understanding of the Sharia and legal aspects of online loans. The inconsistency of certain online loan practices with the principles of muamalah fiqh, such as usury, gharar, and injustice, is examined alongside how the DSN-MUI fatwa offers guidelines for addressing these issues. These findings underscore the importance of strict Sharia regulations and public education to ensure that online loan transactions adhere to Islamic principles. There is a pressing need to strengthen the DSN-MUI fatwa as a reference for Sharia law in online loans, while also recommending that regulators and businesses comply with the principles of fiqh muamalah. Additionally, emphasizing the significance of public awareness about Sharia-compliant online loans is crucial. This conclusion ties the findings back to the research objectives and suggests directions for future research or policies.